ANALISA PENGUJIAN GESEK, AUS DAN LENTUR PADA KAMPAS REM TROMOL SEPEDA MOTOR - Sumiyanto Sumiyanto; Abdunnaser Abdunnaser; Achmad Noor Fajri (Bina Teknika, 2019)
This analisys who does are to point off base on motorcycle community to able learning education such as purpose and quality of break kanvas with standardization even chossing of material pad kanvas who does no failed of chossing as performance capability in  deserasy of speed. For knowing for that, firtable we must to analyzing of performance and compared. In this section are used two of sample with deference kind of material, such as non asbestos (semi metallic). For in this case we take a tree experiment, like measuring analyse, threadbare and scrape. Of the end analyse that could knowing are using material non asbestos (semi metallic) are excelellen better than asbestos kanvas as orientation SNI number 09-9134-1987. As you know share, using far away way are suitable in non asbestos and recomanded.